2022
DOI: 10.1016/j.ijom.2021.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Assault-related facial fractures: does the injury mechanism matter?

Abstract: This study clarified the injury characteristics and occurrence of associated injuries in patients with assault-related facial fractures. Data from 840 assaultrelated facial fracture patients were included; demographic factors, facial fracture type, associated injuries, alcohol use, and injury mechanisms were recorded. Assault mechanisms most often included combinations of different mechanisms (57.5%) and resulted in the victim falling (50.1%). The perpetrator was most commonly a stranger (52.5%) and acted alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
(44 reference statements)
0
3
0
Order By: Relevance
“…Several studies have shown that motor vehicle accidents are the leading cause of maxillofacial fractures in young adults 46 , 47 . This age group is also more likely to engage in physical altercations, which can result in maxillofacial trauma 48 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that motor vehicle accidents are the leading cause of maxillofacial fractures in young adults 46 , 47 . This age group is also more likely to engage in physical altercations, which can result in maxillofacial trauma 48 .…”
Section: Discussionmentioning
confidence: 99%
“…This again supports the argument that MVAs are the primary cause of mandibular fractures in Iran, as these accidents typically result in high-impact forces that affect the mandibular body and condyle 60 . In contrast, physical assaults typically result in fractures of the zygomatic arch or orbital bones, as these areas are more exposed and vulnerable to direct impact 48 .…”
Section: Discussionmentioning
confidence: 99%
“…Upper limb fractures were the commonest in assaults as shown in this study could be due to natural defense mechanisms to protect themselves using upper limbs. The surveyed literature describes facial bone injuries as the common injuries in assaults [19,20].…”
Section: Discussionmentioning
confidence: 99%